Conductive Zn(ii)-metallohydrogels: the role of alkali metal cation size in gelation, rheology and conductance. Issue 8 (2nd July 2021) - Mahendar, Chinthakuntla; Kumar, Yeeshu; Dixit, Manish Kumar; Mukherjee, Moupia; Kalam, Abul; Dubey, Mrigendra
Abstract : Studies of metallohydrogels comprehended the relation about smaller the size of the alkali metal ions, stronger the metallohydrogel matrix and weaker the conductivity of metallogel. Abstract : In the present report, a series of conductive metallohydrogels MH-Li, MH-Na, MH-K and MH-Cs (0.6% w/v) have been synthesized by deprotonation of a terephthalohydrazide derived ligand o -H 4 TEP using alkali bases MOH (M = Li + /Na + /K + /Cs + ), followed by reaction with Zn(NO3 )2 ·6H2 O. The as-synthesized metallohydrogels have been thoroughly characterized via FT-IR spectroscopy, 1 H NMR, UV-vis, fluorescence, ESI-mass spectrometry, FE-SEM, TEM, PXRD, TGA and rheological experiments to investigate the effect of size of alkali metal ions as well as the underlying mechanism of the gelation of the metallohydrogel. Rheological and EIS measurements were performed to explore the effects of alkali metal ion size and establish the correlation between the gelation behaviour and conductance property of the as-synthesised metallogels. An increment in the conductivity value of metallogels from 1.55 × 10 −2 S cm −1 for MH-Li to 4.9 × 10 −2 S cm −1 for MH-Cs has been observed upon increasing the alkali metal ion size, which is in accordance with the decline in the rheological properties of the metallogels. Also, the conductivity of all the synthesised metallogels was found to increase with temperature.